Design and Development of Social Assistance Applications Mobile-Based Using Extreme Programming (XP) Methods at the Ministry of Religion of Medan City - Nababan, Yusuf Walhadi Rama Putra; Alda, Muhamad (UIN Sumatera Utara, 2025)
The Medan City Ministry of Religion Office is a state ministry that provides social assistance services to the community. In carrying out the distribution of social assistance to the community, the Medan City Ministry of Religion Office has not yet provided a system, so the distribution and recording process is still carried out conventionally. In distributing social assistance zakat, the Ministry of Religion still records each aid recipient in a book, so there are still problems in terms of searching for data which takes a long time, data damage, data loss and the possibility of entering the same data (data redundancy). Therefore, the aim of this research is to build a mobile-based application to make it easier to record and monitor the distribution of social assistance to the community. The system development method used is the Extreme Programming (XP) method which consists of the Planning, Design, Coding and Testing stages. Meanwhile, the tool used by the author in creating information system designs visually is UML (Unified Modeling Language). This mobile-based application was built using Android Studio tools and a MySQL database. With this application, it is hoped that it can help the Medan City Ministry of Religion Office to record and monitor the distribution of social assistance to the community easily and quickly via Android cellphones.